2018
DOI: 10.1371/journal.pcbi.1005896
|View full text |Cite
|
Sign up to set email alerts
|

Clustering gene expression time series data using an infinite Gaussian process mixture model

Abstract: Transcriptome-wide time series expression profiling is used to characterize the cellular response to environmental perturbations. The first step to analyzing transcriptional response data is often to cluster genes with similar responses. Here, we present a nonparametric model-based method, Dirichlet process Gaussian process mixture model (DPGP), which jointly models data clusters with a Dirichlet process and temporal dependencies with Gaussian processes. We demonstrate the accuracy of DPGP in comparison to sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
120
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 78 publications
0
120
0
Order By: Relevance
“…E). We next used the nonparametric Dirichlet process Gaussian process mixture model to cluster fold changes in aligned reads (normalized to transcripts per million [TPM]) to assess changes in gene expression patterns associated with cell cycle progression. A total of 2,972 differentially expressed genes (false discovery rate (FDR) < 0.05) underwent clustering and 10 clusters emerged (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…E). We next used the nonparametric Dirichlet process Gaussian process mixture model to cluster fold changes in aligned reads (normalized to transcripts per million [TPM]) to assess changes in gene expression patterns associated with cell cycle progression. A total of 2,972 differentially expressed genes (false discovery rate (FDR) < 0.05) underwent clustering and 10 clusters emerged (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A correlation circle map was created using the R circlize package [32]. The clustering of expression trends was performed using Python DP_GP [33].…”
Section: Experimental Methods Correlation Analysis Of Transcript Exprmentioning
confidence: 99%
“…Using principal component analysis (PCA), we found that the strongest source of variation was in treatment vs control (PC1), followed by phase of the cell cycle (PC2) ( Figure 1E). We next used the nonparametric Dirichlet process Gaussian process mixture model (DPGP) 26 to cluster fold changes in aligned reads (normalized to transcripts per million (TPM)) to assess changes in gene expression patterns associated with cell cycle progression. A total of 2972 differentially expressed genes (FDR < 0.05) underwent clustering and 10 clusters emerged ( Figure 1F) with genes upregulated or downregulated in response to phase of the cell cycle following the DMSO treatment.…”
Section: Gene Expression Dynamics Associated With Cell Cycle Progressmentioning
confidence: 99%
“…Differential genes underwent clustering with the Dirichlet process Gaussian process mixture model DPGP 26 software. 1000 iterations of clustering were performed with default software parameters.…”
Section: Rna-sequencing Processing Pipelinesmentioning
confidence: 99%